Stability Analysis of Bagong Maindam using Geostudio - Fakhruddin, Daffa Budi; Marsudi, Suwanto; Cahya, Evi Nur; Nurjati Hidayat, Muhammad (Fakultas Teknik, Universitas Brawijaya, 2024)
This research investigates the stability and seepage analysis of Bagong Dam, which is an important factor in dam planning. The planned dam must withstand various loads and forces acting on it. Seepage analysis was conducted using the Seep/W program in Geostudio software. For dam stability analysis, the Bishop Method was utilized with the assistance of the Slope/W program in Geostudio software. The safety factor (SF) in seepage analysis and dam stability must meet the required threshold to confirm the dam's safety. The results of the seepage analysis for Bagong Dam indicate safety, as the seepage discharge (QNWL = 0.005018039 m3/s; QFWL = 0.005412454 m3/s; and QMWL = 0.002444141 m3/s) is less than 1% of the Bagong River inflow discharge (0.06791 m3/s). In the stability analysis, the safety factor (SF) results for the dam under conditions without earthquakes and 100 and 200-year Operational Based Earthquakes (OBE) indicate that the dam is safe. However, the dam is considered unstable under an earthquake load with a return period of 10,000 years (Maximum Design Earthquake, MDE). Deformation analysis using the Makdisi and Seed Method was performed to ensure its safety. The results indicated that the maximum displacement was less than permissible, indicating that the dam is safe.